The Relationship Between Sleep Quality and Depression Level in Students During the Covid-19 Pandemic Period - Permatananda, Pande Ayu Naya Kasih; Yamamoto, Sota; Kobayashi, Riko (World Psychology, 2025)
The Covid-19 pandemic has caused significant disruptions in daily life, leading to various mental health challenges, particularly among students. Sleep quality and depression are closely related, with poor sleep often contributing to higher levels of depression. During the pandemic, changes in daily routines, increased stress, and social isolation have likely affected both sleep patterns and mental health. This study aims to investigate the relationship between sleep quality and depression levels in students during the Covid-19 pandemic period. A cross-sectional design was employed, with 300 university students completing an online survey. Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI), and depression levels were measured with the Patient Health Questionnaire-9 (PHQ-9). The results indicated that students reporting poor sleep quality had significantly higher depression scores compared to those with better sleep quality. A negative correlation was found between sleep quality and depression levels, with poorer sleep associated with higher depression severity. The study concludes that poor sleep quality is a significant predictor of increased depression in students during the pandemic. These findings emphasize the need for interventions targeting sleep improvement as part of mental health support for students during and beyond the Covid-19 crisis.